Reconstructing the ancestral gene pool to uncover the origins and genetic links of Hmong–Mien speakers - Yang Gao; Xiaoxi Zhang; Hao Chen; Yan Lu; Sen Ma; Yajun Yang; Menghan Zhang; Shuhua Xu (BMC Biology, 2024)
Abstract Background Hmong–Mien (HM) speakers are linguistically related and live primarily in China, but little is known about their ancestral origins or the evolutionary mechanism shaping their genomic diversity. In particular, the lack of whole-genome sequencing data on the Yao population has prevented a full investigation of the origins and evolutionary history of HM speakers. As such, their origins are debatable. Results Here, we made a deep sequencing effort of 80 Yao genomes, and our analysis together with 28 East Asian populations and 968 ancient Asian genomes suggested that there is a strong genetic basis for the formation of the HM language family. We estimated that the most recent common ancestor dates to 5800 years ago, while the genetic divergence between the HM and Tai–Kadai speakers was estimated to be 8200 years ago. We proposed that HM speakers originated from the Yangtze River Basin and spread with agricultural civilization. We identified highly differentiated variants between HM and Han Chinese, in particular, a deafness-related missense variant (rs72474224) in the GJB2 gene is in a higher frequency in HM speakers than in others. Conclusions Our results indicated complex gene flow and medically relevant variants involved in the HM speakers’ evolution history.